Pengaruh Persepsi Konsumen terhadap Keputusan Pembelian Produk Private Brand Indomaret (Studi pada Konsumen Indomaret di Jalan Raya Pendidikan Kecamatan Rappocini Kota Makassar) - Latifah Asmil Fauzi; Muh. Ihsan Said; Mustari Mustari; Tuti Supatminingsih; Muhammad Hasan (Indonesian Journal of Pedagogical and Social Sciences, 2021)
Abstract. This study aims to determine the effect of consumer perceptions in this case price perceptions and quality perceptions on purchasing decisions for Indomaret private brand products on Jalan Raya Pendidikan, Rappocini District, Makassar City. This research is a descriptive quantitative research. The population in this study were all consumers of Indomaret on Jalan Raya Pendidikan whose number could not be determined and a sample of 100 respondents was obtained. Data was collected by means of observation and questionnaires. The analysis technique used is multiple linear regression. The results of this study indicate that perceived price and perceived quality have a significant positive effect on purchasing decisions for Indomaret private brand products, either partially or simultaneously. Keywords: Consumer Perception, Price Perception, Quality Perception, and Purchasing Decision